Managing risks of nitrates to humans and the environment - Wilson, W. S.; Ball, A. S.; Hinton, R. H. (Special Publication ;, 1999)
This volume concentrates on research information on the beneficial effects of nitrates and their fate in the environment. Adopting an integrated approach it covers the agricultural, environmental and medical aspects of this emotive topic. In addition, there is an extensive description of the biochemistry of nitrates in plants, animals and humans including the positive aspects as well as the hazards.